Within-city roads and urban growth - Brandily, Paul; Rauch, Ferdinand (Journal of regional science, 2024)
In this paper we study the role of within-city roads layout in fostering city growth. Within-city roads networks have not been studied extensively in economics although they are essential to facilitate human interactions, which are at the core of agglomeration economies. We build and compute several simple measures of roads network and construct a sample of over 1800 cities and towns from Sub-Saharan Africa. Using a simple econometric model and two instrumental variable strategies based on the history of African cities, we then estimate the causal impact of within-city roads layout on urban growth. We find that over the recent decades, cities with greater road density and road evenness in the centre grew faster.